PERCEIVED GAPS IN 21ST-CENTURY SKILLS DEVELOPMENT AMONG PRE-SERVICE ENGLISH TEACHERS IN UZBEKISTAN: A PILOT NEEDS ANALYSIS - Baxromova Irodaxon Bobirxon qizi (International Journal of Literature and Language Studies, 2026)
This pilot study explores how pre-service English teachers in Uzbekistan view the significance, development, and curriculum-based support of 21st-century skills. It addresses a gap in research on English language teacher education in Central Asia, where competence-based reforms are frequently discussed at the policy level but rarely investigated from the perspective of student experiences. Data were gathered through surveys from 190 undergraduates enrolled in English teaching programs. The survey included demographic information, two needs-assessment questions, and 25 items assessing curriculum support across five domains: creativity, critical thinking, communication, collaboration, and information, media, and technology skills. The analysis employed frequency counts, descriptive statistics, reliability testing, Pearson correlations, and one-way ANOVA. Findings reveal a disconnect between the skills students consider most important and those they believe they have developed. While critical thinking was ranked as the most valuable skill, communication was seen as the area with the greatest improvement. Although overall curriculum support ratings were moderate to high, critical thinking received the lowest average score. The results indicate that teacher training programs should go beyond broad mentions of 21st-century competencies and instead offer more targeted instruction in analytical reasoning, digital teaching methods, collaborative professional development, creative assessment strategies, and performance-based reflection.